2023
DOI: 10.1001/jama.2023.4480
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Angiotensin-Converting Enzyme Inhibitor and Angiotensin Receptor Blocker Initiation on Organ Support–Free Days in Patients Hospitalized With COVID-19

Abstract: IMPORTANCEOveractivation of the renin-angiotensin system (RAS) may contribute to poor clinical outcomes in patients with COVID-19.ObjectiveTo determine whether angiotensin-converting enzyme (ACE) inhibitor or angiotensin receptor blocker (ARB) initiation improves outcomes in patients hospitalized for COVID-19.DESIGN, SETTING, AND PARTICIPANTSIn an ongoing, adaptive platform randomized clinical trial, 721 critically ill and 58 non–critically ill hospitalized adults were randomized to receive an RAS inhibitor or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 66 publications
1
23
0
Order By: Relevance
“…13,16,17,20,126,127 The REMAP-CAP trial (NCT02735707) administered either ACE inhibitors (232 patients; 35% women), conventional AT 1 R antagonists (218 patients; 30% women), or standard care (231 controls; 39% women) to COVID-19 patients with pneumonia. 128 REMAP-CAP was also terminated early as both treatments exhibited worse outcomes (survival and intensive care support) than the control group. Moreover, a significant proportion of patients on RAS blockers (>40%) discontinued treatment due to a decline in blood pressure.…”
Section: Sex Differences In Acute Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…13,16,17,20,126,127 The REMAP-CAP trial (NCT02735707) administered either ACE inhibitors (232 patients; 35% women), conventional AT 1 R antagonists (218 patients; 30% women), or standard care (231 controls; 39% women) to COVID-19 patients with pneumonia. 128 REMAP-CAP was also terminated early as both treatments exhibited worse outcomes (survival and intensive care support) than the control group. Moreover, a significant proportion of patients on RAS blockers (>40%) discontinued treatment due to a decline in blood pressure.…”
Section: Sex Differences In Acute Covid-19mentioning
confidence: 99%
“…Moreover, a significant proportion of patients on RAS blockers (>40%) discontinued treatment due to a decline in blood pressure. 128 Although the characterization of the NECTAR and REMAP-CAP trials regarding the status of the RAS in both females and males should be forthcoming, early termination of these RAS treatment trials does not support a critical role of the RAS (greater Ang II or reduced Ang- [1][2][3][4][5][6][7]) in the acute phase of SARS-CoV-2 infection nor explain sex differences in COVID-19 severity.…”
Section: Sex Differences In Acute Covid-19mentioning
confidence: 99%
“…Gaining insight into how treatments influence cardiovascular risk after infections is also pivotal. Although randomized trials have not shown benefits from interventions like statins, angiotensin-converting enzyme inhibitors, and angiotensin II receptor blockers for patients severely ill with infection, 3,4 they indicate reduced cardiovascular complications with influenza vaccination in patients with preexisting coronary heart disease and reduced mortality with ultrashort-acting β1-blockers in treating sepsis. 5 Systematic assessment of the benefits, drawbacks, and cost-effectiveness of population-wide and targeted strategies, and personalized interventions, as well, is warranted.…”
Section: In Responsementioning
confidence: 99%
“…Two of the RAS modulation strategies evaluated as potential therapeutic avenues for COVID-19 are angiotensin II type 1 receptor blockade and exogenous administration of angiotensin (1-7). Agents that block angiotensin II type 1 receptor have resulted in trends toward worse outcomes in 3 recent COVID-19 trials: for losartan in the ALPS-IP trial, for an angiotensin-converting enzyme inhibitor or angiotensin receptor blocker in the REMAP-CAP platform, and for an angiotensin II type 1 receptor–biased ligand (TRV-027) in 1 of the 2 trials reported by us (the ACTIV-4 Host Tissue Investigators). Thus, we believe that angiotensin II type 1 receptor blockade in COVID-19 does not need further study.…”
mentioning
confidence: 99%